A detailed analysis of 'not relevant' responses on the DLQI in psoriasis: potential biases in treatment decisions. (28th November 2017) - Rencz, F.; Poór, A.K.; Péntek, M.; Holló, P.; Kárpáti, S.; Gulácsi, L.; Szegedi, A.; Remenyik, É.; Hidvégi, B.; Herszényi, K.; Jókai, H.; Beretzky, Z.; et al.
Abstract: Background: Dermatology Life Quality Index (DLQI) is the most common health‐related quality of life measure in dermatology that is widely used in treatment guidelines for psoriasis. Eight of the 10 questions of the DLQI offer a 'not relevant' response (NRR) option that is scored as the item had no impact on patients' life at all. Objective: To explore the occurrence of NRRs on the DLQI in psoriasis patients and to examine the effect of several socio‐demographic and clinical factors on giving NRRs. Methods: Data were obtained from two cross‐sectional surveys among psoriasis patients at two academic dermatology clinics in Hungary. Health‐related quality of life was measured by employing DLQI and EQ‐5D‐3L, while disease severity was graded by Psoriasis Area and Severity Index (PASI). Multivariate logistic regression was applied to determine the predictors of providing NRRs. Results: Mean age of the 428 patients was 49 years, and 65% were males. Mean PASI, DLQI and EQ‐5D‐3L index scores were 8.4 ± 9.5, 6.8 ± 7.4 and 0.74 ± 0.28, respectively. Overall, 38.8% of the patients had at least one NRR: 19.6% (one), 11.5% (two), 5.1% (three) and 2.6% (more than three). Most NRRs occurred in sport, sexual difficulties and working/studying items of the DLQI (28.4%, 16.4% and 14.0%, respectively). Female gender (OR 1.65; 95% CI 1.04–2.61), older age (OR 1.05; 95% CI 1.03–1.07) and higher PASI score (OR 1.03; 95% CI 1.01–1.06) were associated with providing more NRRs, whereas highly educated patients (OR 0.34; 95% CI 0.16–0.72) and those with a full‐time job (OR 0.47; 95% CI 0.29–0.77) less frequently tended to tick NRRs. Conclusion: The high rate of psoriasis patients with NRRs, especially among women, less educated and elderly patients, indicates a content validity problem of the measure. A reconsideration of the use of the DLQI for medical and financial decision‐making in psoriasis patients is suggested.